2019
DOI: 10.5194/nhess-19-1151-2019
|View full text |Cite
|
Sign up to set email alerts
|

Towards measuring resilience of flood-prone communities: a conceptual framework

Abstract: Abstract. Community resilience has become an important policy and research concept for understanding and addressing the challenges associated with the interplay of climate change, urbanization, population growth, land use, sustainability, vulnerability and increased frequency of extreme flooding. Although measuring resilience has been identified as a fundamental step toward its understanding and effective management, there is, however, lack of an operational measurement framework due to the difficulty of syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Various indicators have been offered to assess flood resilience in different cities. Oladokun and Montz (2019) proposed a conceptual framework for assessing flood resilience in the United States. They explained three dimensions for analysis, including (1) risk absorption capacity, (2) access to resources, and (3) community processes and resource use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various indicators have been offered to assess flood resilience in different cities. Oladokun and Montz (2019) proposed a conceptual framework for assessing flood resilience in the United States. They explained three dimensions for analysis, including (1) risk absorption capacity, (2) access to resources, and (3) community processes and resource use.…”
Section: Introductionmentioning
confidence: 99%
“…They explained three dimensions for analysis, including (1) risk absorption capacity, (2) access to resources, and (3) community processes and resource use. Their findings indicated that the proposed framework is an appropriate method for assessing flood resilience, even in the case of limited data availability and relevance [41]. Campbell et al (2019) also developed a tool to assess flood resilience in large communities.…”
Section: Introductionmentioning
confidence: 99%
“…This is a soft computing analytical technique that has already been used extensively in environmental risk assessments (e.g. Seguí et al 2013) and has also been recently applied in resilience evaluation of flood-prone communities (Oladokun and Montz 2019), among other applications.…”
Section: Model Descriptionmentioning
confidence: 99%
“…This monumental shift is majorly from the mindset of flood prevention to flood risk mitigation (Schelfaut et al, 2011;Batica et al, 2013). The concept of resilience is central to this thinking and has now become a focus of flood risk management with its usefulness being extended to the planning of the environment and decision making (Hammond et al, 2015;Oladokun & Montz, 2019).…”
Section: Originality/valuementioning
confidence: 99%